2013
DOI: 10.3402/gha.v6i0.19090
|View full text |Cite
|
Sign up to set email alerts
|

Medical causes of admissions to hospital among adults in Africa: a systematic review

Abstract: BackgroundDespite the publication of several studies on the subject, there is significant uncertainty regarding the burden of disease among adults in sub-Saharan Africa (sSA).ObjectivesTo describe the breadth of available data regarding causes of admission to hospital, to systematically analyze the methodological quality of these studies, and to provide recommendations for future research.DesignWe performed a systematic online and hand-based search for articles describing patterns of medical illnesses in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
61
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 40 publications
5
61
1
Order By: Relevance
“…The rate of improved and discharged patients (78.0%) was similar to the rate reported in a tertiary health centre in Nigeria, but lower than rates reported from hospitals in Ethiopia and Sudan. 1,6,18 In most cases, the average duration of hospital stay in the current study was one week or less (86.3%), which is consistent with similar studies carried out in Khartoum and Pakistan. 6,15 This could be explained by the fact that most acute communicable diseases, as well as uncomplicated NCDs, are treatable within this short timeframe.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The rate of improved and discharged patients (78.0%) was similar to the rate reported in a tertiary health centre in Nigeria, but lower than rates reported from hospitals in Ethiopia and Sudan. 1,6,18 In most cases, the average duration of hospital stay in the current study was one week or less (86.3%), which is consistent with similar studies carried out in Khartoum and Pakistan. 6,15 This could be explained by the fact that most acute communicable diseases, as well as uncomplicated NCDs, are treatable within this short timeframe.…”
Section: Discussionsupporting
confidence: 91%
“…[12][13][14] However, findings from studies carried out in Ethiopia, Sudan and Pakistan indicated that communicable diseases were more prevalent. 1,6,15 The change from communicable diseases to NCDs in the hospital admission patterns observed in the current study could be explained by the fact that more than half of the admitted patients were from urban areas. Increasing urbanisation can result in reduced physical activity, dietary changes and a rise in the rate of obesity.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…These include a changing school education system where disparate pedagogical approaches have been implemented over the last decade; [2] a changing patient population, with the emergence of previously neglected or unknown diseases; [3] and a lack of available resources, making clinical insight even more important as the primary tool available to healthcare workers. Consequently, long-established didactic approaches to the teaching of physiology may no longer fully meet the needs of current students or fulfil the demands for effective training of healthcare professionals.…”
mentioning
confidence: 99%
“…Stroke is the main cause of CVD deaths [4]. CVD has progressed in SSA [5,6]; coronary heart diseases are not infrequent [79]; stroke incidence varies from 35 to 108/100,000 person-years [10–12]. Asymptomatic PAD prevalence was estimated at around 10% [1315].…”
Section: Introductionmentioning
confidence: 99%